Logic Petri Net Synthesis for Cooperative Systems - Wenjing Luan (IEEE Access, 2019)
Logic Petri Nets (LPNs) is a high-level Petri net, which have the capability to model the batch and indeterminate processing of resources in cooperative systems. Their modeling capability is equivalent to that of inhibition Petri nets (IPNs) but the former maintains simpler net structures. This paper presents a systematic LPN synthesis approach for cooperative systems. First, a normal/logic transition with its connected places is treated as a basic design module. Then, we synthesize the basic design modules firstly to construct LPN models by connecting with shared resource places. Finally, some control strategies are designed to guarantee the resulting LPNs with desirable properties such as boundedness, liveness, and reversibility. An example for constructing an E-commerce system is proposed to illustrate the proposed approach. The paper is of significance in the sense that it provides industrial engineers and academic researchers a methodology of applying LPNs to modeling and analysis of cooperative systems.